2021
DOI: 10.1155/2021/8864051
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Airborne Bacterial and Fungal Communities in Shahrekord Hospitals

Abstract: This paper presents information about airborne microorganisms (bacteria and fungi) in the indoor air of two hospitals (Kashani and Hajar) in the city of Shahrekord, Iran. The settle plate technique using open Petri dishes containing different culture media was employed to collect a sample and using Quick Take 30 Sample Pump three days per week for a period of 8 weeks. Standard microbiological methods were employed for the identification of bacterial and fungal isolates. The results showed that the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Other pathogenic fungal taxa identified as core mycobiota in FC and FV samples were genera Pseudallescheria ( Luplertlop, 2018 ), Candida ( Turner and Butler, 2014 ), and Diutina ( Chen et al, 2021 ). The diversification of fungal in the HCW may be linked with mycological contamination in the air and on the surface, which has been frequently observed in hospital settings and might contribute to fungal infections ( Jackson and Chiller, 2018 ; Jalili et al, 2021 ). Our results contradicted the findings of Kollu et al (2022) and Wang et al (2020) , who reported that microwave radiation can effectively destroy fungi as demonstrated by microbial log reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathogenic fungal taxa identified as core mycobiota in FC and FV samples were genera Pseudallescheria ( Luplertlop, 2018 ), Candida ( Turner and Butler, 2014 ), and Diutina ( Chen et al, 2021 ). The diversification of fungal in the HCW may be linked with mycological contamination in the air and on the surface, which has been frequently observed in hospital settings and might contribute to fungal infections ( Jackson and Chiller, 2018 ; Jalili et al, 2021 ). Our results contradicted the findings of Kollu et al (2022) and Wang et al (2020) , who reported that microwave radiation can effectively destroy fungi as demonstrated by microbial log reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The floor space per inmate (m²/person) significantly affects the concentration of S. aureus negatively ( P = .032). This is due to the bacterial load being attributed to the number of occupants as a human is a reservoir of S. aureus 31 when they are released by different occasional activities like sneezing, coughing, and talking. 12 , 13 However, the number of occupants by itself cannot affect microbial load in the indoor environment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers have been published about airborne microbes in hospital environments [ 2 , 9 , 10 , 11 ]. Studies on bacterial concentrations in the air show a considerable variation in abundance and species diversity between locations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bacterial concentrations in the air show a considerable variation in abundance and species diversity between locations. Nevertheless, some species are commonly found in most sites, including Staphylococcus , Bacillus , and Micrococcus [ 9 , 11 , 12 , 13 ]. Airborne transmission is a known route for multiple highly threatening infectious microbes, such as methicillin-resistant Staphylococcus aureus (MRSA), Mycobacterium tuberculosis , and multi-drug-resistant Acinetobacter spp., that have been isolated from health care facility environments [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%